Deep Eutectic Solvent (Des) As A New Solvent For Lipase-Catalyzed Synthesis Of Glyceryl Monocaffeate Via Transesterification - Bakar, Puteri Norathirah Megat Abu (2019)
Ionic liquids and deep eutectic solvent (DES) have been identified as greener alternatives solvents. Nevertheless, ionic liquid has been reported to display toxicity to the environment due to its starting material (i.e. imidazolium-based cation). Therefore, the design of DES for ionic liquids substitution has shown a bright future for implementation in lipase-catalyzed reaction. Lipase-catalyzed reaction of glyceryl monocaffeate (GMC) in DES has not yet been reported. The modification of caffeic acid (CA) into GMC could potentially be widen the application of CA’s biological activities in water and oil-based system. The transesterification of ethyl caffeate (EC) and glycerol to produce GMC was carried out by screening these parameters that affect the reaction such as enzyme loading between 250 U to 1500 U, water content within 0 % (v/v) and 40 % (v/v), agitation speed ranged from 100 rpm to 250 rpm, substrates molar ratio of ethyl caffeate and glycerol from 1:40 to 1:90, reaction time between 0 to 240 minutes and temperatures ranged from 30 ºC to 60 ºC. Final conversion of ethyl caffeate at 88.4% was obtained at 1250 U of enzyme loading, 20 % (v/v) of water content, 200 rpm of agitation speed, 1:50 substrates molar ratio of ethyl caffeate and glycerol, 30 minutes of reaction time and 40 ºC of temperature. The kinetic mechanism and kinetic parameters were investigated to determine the initial rate of reaction of various substrates concentration. The results demonstrated that lipase-catalyzed synthesis of GMC in DES obeyed Ping Pong Bi Bi mechanism with Vmax, 10.9 mmol min-1; KmEC, 126.5 mmol and KmGly, 1842.7 mmol. Next, the study on the activation energy was conducted by varying temperature from 30 ºC to 55 º C and resulted in the value of activation energy was 50.4 kJ/mol. Finally, response surface methodology (RSM) based on face-centered central composite design (CCD) was studied to obtain the following optimum conditions with 94.71±0.06 % final conversion of EC from significant factors: enzyme loading, 705 U; water content, 20 % (v/v) and reaction time, 113 minutes. Therefore, it can be concluded that DES could serve as a potential solvent for lipase-catalyzed reaction.